Correlation between pedicle size and the rate of pedicle screw misplacement in the treatment of thoracic fractures: Can we predict how difficult the task will be?. (4th July 2015) - Gonzalvo, Augusto; Fitt, Gregory; Liew, Susan; de la Harpe, David; Vrodos, Nikitas; McDonald, Matthew; Rogers, Myron A.; Wilde, Peter H.
Abstract: Study Design. A retrospective study. Objective. To correlate the incidence of pedicle-screw (PS) misplacement with the dimensions of the pedicles in the treatment of thoracic spine fractures. Summary of background data . The technical challenge of internal fixation with PS in the thoracic spine has been well documented in the literature. However, there are no publications that document the correlation between the pedicle dimensions of the thoracic vertebrae in the preoperative computed tomography scans (CT) and the rate of PS misplacement. Methods . All patients who had PSs inserted between the T1 and T12 vertebrae during a 24-month period were included in this study. PS position was assessed on high quality CT scans by two independent observers and classified in 2 categories: correct or misplaced. The transverse diameter, craniocaudal diameter and cross-sectional area of the pedicles from T1 to T12 were measured in the pre-operative CT. Results . During the period of this study 36 patients underwent internal fixation with 218 PS. Of the 218 screws, 184 (84.5%) were correct and 34 (15.5%) were misplaced. Misplacement rate was 33% for pedicles with a transverse diameter less than 5 mm, 10.7% for those with a transverse diameter between 5 and 7 mm and 0% for those with a transverse diameter larger than 7 mm. There was a statistically significant difference in the rate of PS misplacement in pedicles with transverse diameter smaller than 5 mm compared with the others. Also, those with transverse diameter between 5.1 and 7 mm compared with those bigger than 7 mm in diameter. The rate of PS misplacement was higher between T3 and T9 (p < 0.05), which in turn correlated with pedicle transverse diameter. Conclusion. The rate of PS misplacement in the mid thoracic spine (T4–T9) is high and correlates with pedicle transverse diameter.